2021
DOI: 10.1002/batt.202100174
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Processing by Design of High‐Nickel Cathode Materials

Abstract: The high demand of lightweight, high energy density batteries for energy storage promotes new materials discovery and development. Despite the large number of battery materials being discovered, very few of them have been commercially deployed, mostly bottlenecked by synthesis and processing – namely, making certain phases with the desired structure and properties to meet the multifaceted performance requirements. Alternative to the traditional trial and error, we present here an in situ study aided synthesis‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…In situ XRD has widely been used to study the synthesis of NCMbased layered oxides as summarized in a recent review. 24 In our study, we show that the simple blending of binary transition metal oxides and the use of Li 2 CO 3 as Li-source is perfectly suited to obtain SC-NCM83 in the same structural quality as in case of the conventional precursors already after a few hours of calcination at 900 °C. Furthermore, we investigate the influence of synthesis temperature on structure, particle size and electrochemical performance and find that calcination at 975 °C for 9 h yields a particle size of 2-3 μm and good electrochemical performance with a discharge capacity of 199 mAh g −1 in the first cycle at 0.05 C.…”
mentioning
confidence: 62%
“…In situ XRD has widely been used to study the synthesis of NCMbased layered oxides as summarized in a recent review. 24 In our study, we show that the simple blending of binary transition metal oxides and the use of Li 2 CO 3 as Li-source is perfectly suited to obtain SC-NCM83 in the same structural quality as in case of the conventional precursors already after a few hours of calcination at 900 °C. Furthermore, we investigate the influence of synthesis temperature on structure, particle size and electrochemical performance and find that calcination at 975 °C for 9 h yields a particle size of 2-3 μm and good electrochemical performance with a discharge capacity of 199 mAh g −1 in the first cycle at 0.05 C.…”
mentioning
confidence: 62%
“…Nickel-manganese-cobalt based cathodes with high Ni content are preferred in Li-ion batteries (LIBs), especially those powering electric vehicles because of their high storage capacity and low cost 1,2 . However, issues persist related to surface reconstruction, oxygen release, transition metal (TM) dissolution, bulk fatigue, and cracking, which precludes their use in practical applications [3][4][5][6][7] . Significant efforts have been made to alleviate these issues over the past decade, with increasing attention paid to high-Ni systemsgenerally represented by LiNi1-x-yMnxCoyO2 and LiNi1-x-yCoxAlyO2 (NMC and NCA, 1-x-y ≥ 0.8) with a layered structure 8,9 .…”
Section: Mainmentioning
confidence: 99%
“…In order to unveil the fundamental mechanism of the surface reconstruction in pristine layered oxides, in situ X‐ray diffraction has been carried out. [ 39 ] Through capturing the structures of samples during cooling process, it was found that surface reconstructions on LROs exhibited a rate‐dependent nature. Li 2 CO 3 was first observed on the surface and then the reconstruction happened during the cooling stage (>350 °C), resulting in the formation of a Li‐deficient spinel layer.…”
Section: In Situ Surface Reconstruction Strategiesmentioning
confidence: 99%